Iklim dan Kepemimpinan Keselamatan Sebagai Pengembangan Perilaku Aman Melalui Sikap Keselamatan Wisata Pantai Biru - Faidal, Faidal; Huwaidah, Huwaidah (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2023)
There is a lack of instructions regarding procedures to be followed by workers in terms of acting for safety and safe behavior. This study aims to establish the influence of a safety climate and safety leadership in the development and management of tourism through a safe attitude towards safety behavior in Pantai Biru Tourism. This study uses a qualitative research approach, with descriptive-qualitative related aspects and in-depth discussion and focus on the subject to be studied. The results of the study explain that the commitment given by the leader will be channeled based on actions in influencing and directing every human resource that contributes to tourism. Safety leadership makes it the responsibility of each worker's awareness and sensitivity to their own safety and security. Based on the theory of Loss Causation Model Bird & Gemain in 1990 in Loss there is something called Injured Worked Time, which is where there is a tragedy or injury experienced by workers and cannot be replaced with work compensation. These findings help leadership and create employee perceptions and commitment to establishing sustainable tourism management policies. Then, the climate dimension of safety leadership needs to be explored in future research with complete data collection. Keywords: Safety Climate, Safety Leadership, Safe Behavior, Safety Attitudes, Tourism